Study of Economic Value of Water for Domestic and Agricultural Uses in Grojogan Sewu Nature Tourism Parkwater Conservation - Dyah, Dyah Arum Kusumaningsih; Suraningsih, Kanti Suraningsih; Dwi , Dwi Sri Nuryanti; Irawan, Arif Irawan; Marciano , Marciano Borges Ximenes; Indah , Indah Susilowati (Jurnal Wasian, 2022)
The water utilization in Grojogan Sewu Nature Tourism Park has been used by community around it to fulfill their water needs such as cooking and farming. In the other hand, it is presumed that they have still lack of awareness and appreciation about the conservation object. One of the efforts to increase the community awareness for the water conservation in Grojogan Sewu Nature Tourism Park is to inform the economic value of the water they use every day. This study aims to analyze the economic value of domestic water use and agricultural irrigation that has been carried out by the community around the Grojogan Sewu TWA area. The research method used in this research is quantitative and qualitative methods. The results showed that the economic value of the use of domestic water and agricultural irrigation by the community around the TWA Grojogan Sewu area was Rp238,565,600,000/month and Rp7,548,750.00/year. This result shows that the economic value of water utilization in TWA Grojogan Sewu is quite high, although the community is not aware of it. This can be illustrated by the value of the community's willingness to pay for the use of water which is still in the fairly low category, which is only Rp7,687,00/month for domestic water use and Rp6,818.00/month for the use of agricultural irrigation.